Greening trade? Environmental provisions in trade agreements - Bettina Meinhart (FIW - Research Centre International Economics, 2022)
International climate targets have far-reaching implications for all areas of the economy and life, including trade policy. To reach the target of the Paris Agreement, it may be necessary to link trade and environmental policy, whereby one way of linking the two policy areas is to include environmental provisions (EPs) in trade agreements. Several motives for including environmental concerns in trade agreements exist, ranging from promoting environmental cooperation and ensuring a level playing field to pursuing protectionist interests. In principle, the inclusion of environmental aspects is not a new development. Since the 1990s, EPs have been frequently integrated into trade agreements, for example on issues such as hazardous waste, deforestation or biodiversity protection. In recent years, as climate initiatives have gained prominence at the EU level, the number of EPs in trade agreements has steadily increased. Thereby, the inclusion of these concerns is very heterogeneous in terms of the subject matter and enforceability. A closer look at the enforceability indicator is crucial, because if EPs are not legally enforceable, addressing environmental concerns may not have an impact on trade and the environment. The European Commission is aware of this issue and therefore published the review of its policy chapter on trade and sustainable development in June 2022. This identifies how the contribution of EU trade agreements to promoting environmental protection can be improved, mentioning, among other actions, the strengthening of enforcement through trade sanctions as a last resort. Whether the current changes are effective in terms of environmental and trade impacts will be seen in further research.
Keywords: 330